2021
DOI: 10.3389/fendo.2021.747944
|View full text |Cite
|
Sign up to set email alerts
|

Brown Adipose Transplantation Improves Polycystic Ovary Syndrome-Involved Metabolome Remodeling

Abstract: Polycystic ovary syndrome (PCOS) is a complex reproductive, endocrine, and metabolic disorder in reproductive-age women. In order to explore the active metabolites of brown adipose tissue (BAT) transplantation in improving the reproductive and metabolic phenotypes in a PCOS rat model, the metabolites in the recipient’s BAT were explored using the liquid chromatography–mass spectrometry technique. In total, 9 upregulated and 13 downregulated metabolites were identified. They were roughly categorized into 12 dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 59 publications
1
3
0
Order By: Relevance
“…Blood phosphatidylcholine can be used as a chemical attractant to recruit immune cells such as macrophages and dendritic cells, thereby improving immune function [ 21 ]. These results were consistent with the conclusion of Yao et al [ 22 ], transplanting the brown adipose tissue in PCOS model mice. GPC/PC was significantly decreased in OB/OW PCOS patients, which was contrary to the conclusion of the previous study [ 18 ].…”
Section: Discussionsupporting
confidence: 93%
“…Blood phosphatidylcholine can be used as a chemical attractant to recruit immune cells such as macrophages and dendritic cells, thereby improving immune function [ 21 ]. These results were consistent with the conclusion of Yao et al [ 22 ], transplanting the brown adipose tissue in PCOS model mice. GPC/PC was significantly decreased in OB/OW PCOS patients, which was contrary to the conclusion of the previous study [ 18 ].…”
Section: Discussionsupporting
confidence: 93%
“…The ability of hiGC to secret human‐derived natural steroid and convert testosterone to estradiol suggested that transplanting hiGC to PCOS individuals may alleviate PCOS syndrome. Although there is study that suggested cell transplantation as a therapeutic strategy for PCOS, 35 we did not find pre‐existing studies that directly use granulosa cells as transplants for PCOS treatment. Therefore, we established a DHEA‐induced PCOS mouse model as previously described 18 and tested the effect of hiGC transplantation on the polycystic ovaries (Figure 7A).…”
Section: Resultsmentioning
confidence: 99%
“…Polycystic ovary syndrome (PCOS) is a serious clinical condition that is related to metabolic and reproductive dysfunction and is characterized by abnormal menstrual cycles, anovulation, insulin resistance (IR), and hyperandrogenemia (HA) [ 1 ]. HA is the primary cause of anovulatory infertility and affects approximately 5–20% of women of childbearing age [ 2 ].…”
Section: Introductionmentioning
confidence: 99%